Composite nanostructure of vertically aligned carbon nanotube array and planar graphite layer obtained by the injection CVD method - Labunov, V.A.; Shulitski, B.G.; Prudnikava, A.L.; Shaman, Y.P.; Basaev, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The carbon nanostructure composed of an array of vertically aligned carbon
nanotubes (CNTs) and a planar graphite layer (PGL) located at the top of the array has
been obtained by the injection chemical vapor deposition method, realized using high
temperature catalytic pyrolysis of xylene-ferrocene mixture. The carbon nature of the
planar layer was identified using Auger electron spectroscopy. Scanning electron
microscopy analysis enabled to ascertain peculiarities of CNT-PGL nanostructure
morphology, in particular, the internal layer-built structure of PGL and its links with the
underlying CNT array. The mechanism of CNT-PGL nanostructure formation was
considered.